Microstructural changes in compressed nerve roots treated by percutaneous transforaminal endoscopic discectomy in patients with lumbar disc herniation. Issue 40 (October 2016) - Wu, Weifei; Liang, Jie; Chen, Ying; Chen, Aihua; Wu, Bin; Yang, Zong
Abstract : Abstract: To investigate the microstructural changes in compressed nerves using diffusion tensor imaging (DTI) of herniated disc treated with percutaneous transforaminal endoscopic discectomy. Diffusion tensor imaging has been widely used to visualize peripheral nerves, and the microstructure of compressed nerve roots can be assessed using DTI. However, the microstructural changes after surgery are not well-understood in patients with lumbar disc herniation. Thirty-four consecutive patients with foraminal disc herniation affecting unilateral sacral 1 (S1) nerve roots were enrolled in this study. DTI with tractography was performed on S1 nerve roots before and after surgery. The mean fractional anisotropy (FA) and apparent diffusion coefficient values were calculated from tractography images. In compressed nerve roots, the FA value before surgery was significantly lower than that after surgery ( P = 0.000). A significant difference in FA values was found between the compressed and normal sides before surgery ( P = 0.000). However, no significant difference was found between the compressed and normal sides after surgery ( P = 0.057). A significant difference in apparent diffusion coefficient values was found before and after surgery at the compressed side ( P = 0.023). However, no significant difference was found between the compressed and normal sides after surgery ( P = 0.203). We show that the diffusion parameters of compressed nerve roots were not significantly different before and after percutaneous transforaminal endoscopic discectomy, indicating that the microstructure of the nerve root recovered after surgery.